2021
DOI: 10.1055/s-0041-1740123
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Analysis of Immediate and Delayed-immediate Breast Reconstruction after Postmastectomy Radiation Therapy

Abstract: Background Postmastectomy radiation therapy (PMRT) is an important component in the treatment of locally advanced breast cancer. Optimal timing of therapy in relation to autologous breast reconstruction (ABR) remains clinically debated. Herein, we comparatively analyze short- and long-term outcomes between immediate ABR (I-ABR) and delayed-immediate ABR (DI-ABR) in the setting of PMRT. Methods Adult patients undergoing ABR with PMRT were separated into cohorts based on reconstructive timeline: I-ABR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 40 publications
2
16
0
Order By: Relevance
“…There have been several reports of increased fat necrosis in reconstructed breasts treated with radiotherapy [14][15][16][17][18] In this regard, immediate-delayed reconstruction has been recommeded as an option to avoid radiation therapy to the autologous reconstruction. [19][20][21] Alternatively, our study found that the volume ratio of the reconstructed breast had no decrease in the radiotherapy group, which was in accordance with other previous reports (p = 0.222, Supplementary Table 1). 22,23 This result may be due to the lower incidence of fat necrosis in our study population.…”
Section: Accepted Manuscriptsupporting
confidence: 93%
“…There have been several reports of increased fat necrosis in reconstructed breasts treated with radiotherapy [14][15][16][17][18] In this regard, immediate-delayed reconstruction has been recommeded as an option to avoid radiation therapy to the autologous reconstruction. [19][20][21] Alternatively, our study found that the volume ratio of the reconstructed breast had no decrease in the radiotherapy group, which was in accordance with other previous reports (p = 0.222, Supplementary Table 1). 22,23 This result may be due to the lower incidence of fat necrosis in our study population.…”
Section: Accepted Manuscriptsupporting
confidence: 93%
“…7 8 The reasons for this include (1) early reports of higher flap complication rates in immediate reconstruction followed by radiation, (2) limitations in treatment planning due to guidelines for postmastectomy radiation based on findings discovered at the time of mastectomy, and (3) potential for the flap to interfere with effective delivery of radiation to the chest wall. 9 10 11 12 22 23 24 25 26 The optimal timing of reconstruction after radiation remains an ongoing debate. Many believe that longer delays allow for recovery of acute inflammatory changes induced by radiation.…”
Section: Discussionmentioning
confidence: 99%
“…Although patient and treatment factors guide discussions and decisions for timing of reconstruction with anticipated radiation therapy (RT), delayed or delayed-immediate reconstruction remains the most common approach with anticipated radiation. 7 8 9 10 11 12 The prevailing assumption is that longer delays are needed to allow sufficient time for recovery of radiation treatment effects to tissues. This is supported by studies reporting higher complications rates when reconstruction is performed before 12 months.…”
mentioning
confidence: 99%
“…This is supported by studies demonstrating that patients who undergo delayed DIEP flap reconstruction in the setting of post-mastectomy radiation therapy experience less complications, such as fat necrosis, as well as less revision procedures. 17 Furthermore, Pittelkow et al showed that some tissue expander patients alter their preference for definitive reconstruction from implants to the DIEP flap. 18 Indeed, in our practice, for patients who know prior to their mastectomy that adjuvant radiation therapy is needed, we recommend a first-stage tissue expander placement as a "babysitter" given the potential radiation induced flap complications and delay the DIEP flap reconstruction until at least 6 months following the conclusion of radiation therapy.…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by studies demonstrating that patients with patients who undergo delayed DIEP flap reconstruction in the setting of post-mastectomy radiation therapy experiences less complications, such as fat necrosis, as well as less revision procedures. 17 Furthermore, Pittelkow et al showed that some tissue expander patients alter their preference for definitive reconstruction from implants to the DIEP flap. 18 Indeed, in our practice, for patients who know prior to their mastectomy that adjuvant…”
Section: Accepted Manuscriptmentioning
confidence: 99%